SITUASI FONOLOGI DALAM KONTEKS WACANA: KASUS JESSICA MIRNA (PATTERN OF PHONOLOGY IN DISCOURSE CONTEXT: JESSICA MIRNA CASE) - Nidya Fitri (SPHOTA: Jurnal Linguistik dan Sastra, 2017)
Abstract This article is aimed at describing form, function, and meaning of phonology in discourse context on Jessica Mirna case. There are three problems of this article are what form, function, is and how pitches of intonation influence meaning of phonology in discourse context: Jessica Mirna case. The designs of this article are descriptive approach and qualitative approach. The source of data in this article is taken from television. Non participant observation method and non participant observation technique are note taking and recording. The function of sign is described and explained by Searle’s theory. Then, meaning of phonology is elaborated by Sack, Schegloff, and Jafferson (1974: 702); Selting (2001): Couper-Kuhlen (2004)’s theories. The result of analysis is concluded; first, it finds form of verbal and nonverbal languages. Second, it finds three forms of functions are (1) representative function; (2) directive function:(3) commissive function. Third, it finds significant influence meaning of phonology in discourse context: Jessica Mirna case are turn talking, pitch control, pause, and rhythm. Key words: phonology, discourse context